Tallinn - Moskva : documendid 1996-1997. - Hrzhanovsky, Andrey; Kabakov, Ilya; Uvarova, Irina; Yankilewsky, Vladimir (Tallinn : Estonian Institute, 1997)
Akberg, Arnold ; Aleksandraksinin ; Annus, Siim-Tanel ; Arrak, Jüri ; Brussilovski, Anatoli ; Bulatov, Erik ; Gerlovin, Rimma & Valery ; Infante, Francisco ; Jankilevskij, Vladimir ; Janov, Valve ; Jõgeva, Villu ; Jõgever, Silva ; Kaasik, Kristiina ; Kabakov, Ilya ; Kärner, Kaja ; Keskküla, Ando ; Kits, Elmar ; Koleitsuk, Vjatseslav ; Komar & Melamid ; Kurismaa, Kaarel ; Lapin, Leonhard ; Leis, Malle ; Liivat-Makarova, Lola ; Lill, Ado ; Makarenko, Vladimir ; Malin, Ilmar ; Maran, Olav ; Meel, Raul ; Nahhova, Irina ; Neizvestnoi, Ernst ; Ohakas, Valdur ; Okas, Jüri ; Ootsing, enno ; Pallo-Vaik, Tiiu ; Pirk, Varmo ; Pivovarov, Viktor ; Poldroos, Enn ; Põllu, Kaljo ; Prigov, Dmitri ; Roode, Henn ; Ruhhin, Jevgeni ; Runge, Sirje ; Sarapuu, Lembit ; Sobolev, Juri ; Sooster, Ulo ; Steinberg, Eduard ; Tammik, Rein ; Tarasov, Vladimir ; Tolts, Andres ; Tsuikov, Ivan ; Vabbe, Ado ; Vardi, Aleksander ; Vassiljev, Oleg ; Vint, Aili ; Vint, Tonis ; Vint, Toomas ; Virve, Tõnu ; Zutovski, Boris
biografie Ilya Kabakov p. 15-17, biografie Vladimir Jankilevski p. 27-29, biografie Vladimir Tarasov p. 21-22
Engels & Ests & Russisch
Tallinn - Moskva, Tallinn Art Hall, Tallinn, 20.12.1996 - 19.01.1997
kunstcatalogus
Keywords: Tallinn; Moskou